Push based buffer setting strategy for high density linecard of small buffer size - LI Yu-feng1; QIU Han1; LAN Ju-long1; WANG Bin-qiang1 (Tongxin xuebao)
Much of the previous work on buffer design of router linecard mainly focus on how to implement large and fast packet buffers,however,lots of recent theories suggest that the optimal buffer size would no longer be a large one as expected,and a small buffer should be sufficient.A push based buffer setting strategy for high density linecard of small buffer size was presented,and a buffer-revenue function was introduced to give an evaluation on using efficiency of the small buffer.It is proved that the strategy can completely eliminate the HOL（header of line） blocking problem and the back-pressure mechanism of the existing strategies,moreover,the strategy can also get a better revenue when the buffer-revenue function is used to give an evaluation.